THE EFFECT OF FINANCIAL REPORTING QUALITY AND FAMILY OWNERSHIP ON INVESTMENT EFFICIENCY WITH AUDIT QUALITY AS MODERATING VARIABLE (Empirical Study on Manufacture Firms Listed on Indonesia Stock Exchange in the Year of 2015-2019) - Joseph Herbert; Puji Harto (Diponegoro Journal of Accounting, 2021)
This study aims to examine the effect of financial reporting quality and family ownership on investment efficiency, moderated by audit quality. Size, leverage, firm age, and tangibility serve as control variables. Population used in this study is manufacture firms listed on Indonesia Stock Exchange (IDX) in the period of 2015-2019 and sample is selected with purposive sampling method, resulting in 251 firms. Statistical analysis in this study is using Structural Equation Model with Partial Least Square (PLS) and Multigroup Analysis (MGA). The results show that family ownership has positive significant effect on investment efficiency, while higher audit quality has positive significant effect on moderating the relationship of family ownership on investment efficiency. Financial reporting quality has negative significant effect on investment efficiency and higher audit quality does not moderate significantly on the relationship of financial reporting quality on investment efficiency.